Importance of cardiac imaging assessment of epicardial adipose tissue after a first episode of myocardial infarction - Islas, Fabián; Gutiérrez, Eva; Cachofeiro, Victoria; Martínez-Martínez, Ernesto; Marín, Gema; Olmos, Carmen; Carrión, Irene; Gil, Sandra; Mahía, Patricia; Cobos, Miguel Ángel; de Agustín, Alberto; Luaces, María (Frontiers in Cardiovascular Medicine, 2022)
Background: Over the past years a rapidly growing amount of information regarding the crosstalk between the epicardial adipose tissue (EAT) and the cardiovascular system has emerged. Particularly, in the context of an acute myocardial infarction, EAT might have a potential role in the pathophysiology of ventricular remodeling and function, as well as with clinical outcome of patients. The aim of this study is to assess the impact of EAT on the outcome of patients after a myocardial infarction (MI). Methods: We studied prospectively admitted patients to our hospital with a first episode of acute MI. All patients underwent percutaneous coronary intervention (PCI) during admission. Transthoracic echocardiography (TTE) was performed within 24-48h after PCI and cardiac magnetic resonance (CMR) was performed 5-7 days after PCI. Clinical follow-up was performed at one and five years after MI. Results: Mean age of our study population (n=41) was 57.5±10 years. Of the total number of patients, 38 (93%) were male. 9 patients had normal BMI, 15 had overweight (BMI 25-30), and 17 were obese (BMI > 30). 23 patients (56%) had >= 4mm thickness of EAT measured with echo. In these patients, baseline left ventricular ejection fraction (LVEF) after AMI was significantly lower, as well as global longitudinal strain. EAT thickness >=4m patients presented larger infarct size, higher extracellular volume and higher T1 times than patients with EAT <4mm. At five-years follow-up 5 patients had major cardiac events, all of them had EAT >=4mm. Conclusions: EAT thickness is a feasible, non-invasive and low-cost parameter that provides important information on the chronic inflammatory state of the myocardium. Patients with EAT >4mm have worse LVEF and GLS, larger infarct size and longer T1 values after MI, and higher levels of Gal-3. EAT >4mm was an independent predictor of MACE at 5-years follow-up.